Agreement among neuropsychological and behavioral data and PiB findings in diagnosing Frontotemporal Dementia. (October 2017) - Ryan, Kelly A.; Hammers, Dustin; DeLeon, Angeline; Bilen, Hande; Frey, Kirk; Burke, James; Albin, Roger; Barbas, Nancy; Heidebrink, Judith; Giordani, Bruno
Highlights: [ 11 C]-PiB PET scan can distinguish between AD and FTD. Patients with behavioral dysfunction may not have FTD if memory deficits are evident. The consistent use of [ 11 C]-PiB PET may enhance the accuracy of clinical diagnoses. Abstract: Diagnostic inaccuracies have been reported in Alzheimer's disease (AD) and Frontotemporal Dementia (FTD) using clinical data alone. The [ 11 C]-PiB PET scan offers a new method of identifying AD based on the detection of amyloid deposits. Our study investigated whether there was an agreement between neuropsychological and behavioral data and PiB findings in the diagnosis of FTD. Participants were 32 patients diagnosed with suspected FTD by clinical consensus. All participants underwent neuropsychological testing and PiB imaging. In addition, caregivers completed behavioral ratings of participants' memory, frontal behaviors, and mood. Seventeen participants were classified as PiB positive (+). Results of MANOVA and subsequent ANOVA analyses showed a significant difference on memory performance between the PiB- and PiB + groups, with the PiB- group performing better than the PiB + group. There were no significant differences between the groups on cognitive or behavioral measures of executive/frontal impairment, mood. Both groups showed similar severity of dementia. These findings provide evidence for the utility of the [ 11 C]-PiB PET scan in distinguishing between AD and FTD, with evaluation of memory at clinical diagnosis serving as a valuable indicator of the absence of FTD and consideration for an AD diagnosis. Our results would support the concern that patients who may present with primary behavioral or executive dysfunction may not necessarily have FTD, particularly if memory deficits are evident.